2004
DOI: 10.1063/1.1629390
|View full text |Cite
|
Sign up to set email alerts
|

Joining of stainless-steel specimens with nanostructured Al/Ni foils

Abstract: We describe the joining of stainless-steel specimens at room temperature using free-standing Al/Ni foils as local heat sources for melting AuSn solder layers. The foils contain many nanoscale layers of Al and Ni that react exothermically, generating a self-propagating reaction. The heats, velocities, and products of the reactions are described, and the microstructure and the mechanical properties of the resulting joints are characterized. Increasing the foil thickness, and thereby increasing the total heat rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
105
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(108 citation statements)
references
References 11 publications
3
105
0
Order By: Relevance
“…Heat release, peak temperature and predicted premixing thickness are listed in Table 1. The total thermal effects calculated from the DSC data are close to the values in references [19,20]. The exotherm of the samples was reduced continuously with decreasing bilayer thickness, which should be ascribed to a larger volume fraction of premixing.…”
Section: Micromorphology and Heat Releasesupporting
confidence: 63%
See 1 more Smart Citation
“…Heat release, peak temperature and predicted premixing thickness are listed in Table 1. The total thermal effects calculated from the DSC data are close to the values in references [19,20]. The exotherm of the samples was reduced continuously with decreasing bilayer thickness, which should be ascribed to a larger volume fraction of premixing.…”
Section: Micromorphology and Heat Releasesupporting
confidence: 63%
“…The peak temperature rose slightly with increasing bilayer spacing, from 231.7 °C to 256.9 °C for the first peak for example, which suggested that longer diffusion distances were indispensable for the Al and Ni atoms to interdiffuse and fully react. The heat released can be used to figure out the premixing thickness, according to the following equation [19]:…”
Section: Micromorphology and Heat Releasementioning
confidence: 99%
“…Wang et al, 3 which studied similar foils, the thickness of the intermixed layer was determined to be 2.3 nm.…”
Section: -mentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20] By comparison, fewer investigations have been undertaken to develop applications for the RMFs. [1][2][3][4][5][6][7] Little is understood regarding the effect of RMFs on neighboring materials (such as a substrate) and the relationship between heat transport in the bulk material and its consequential effect on the microstructure evolution of the ensemble. (Throughout this work, the word "substrate" refers to the bulk Sn-Bi alloy to which the multilayer is bonded through reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation